The classical Greeks - Grant, Michael (New York : Charles Scribner's Sons, 1989)
A history of Greek civilization from the 5th century B.C. to 336 B.C. Focuses on 37 great men of the age.
Includes bibliographical references (p. 313-324).
Booklist
Wilson's Public Library
Adult.
Adult
Keywords: Greece -- Biography; Greece -- Biography; Greece -- History -- Biography; Greece -- History -- To 146 B.C -- Biography